Pengaruh Tingkat Pemahaman Akuntansi, Kualitas Sumber Daya Manusia, Ukuran Usaha, Pemberian Informasi dan Sosialisasi Terhadap Pemahaman UMKM dalam Menyusun Laporan Keuangan Berdasarkan SAK EMKM : Studi Kasus Pada UMKM Di Kota Bogor - Karina Aurelya; Andy Lasmana; Universitas Djuanda (Universitas Dian Nuswantoro, 2024)
Basically, UMKM indirectly plays a role in the absorption of a fairly high labor force, but this UMKM sat is faced with constraints regarding the limited production of appropriate reports. UMKM has yet to understand how to manage finances and the importance of presenting financial statements. EMKM SAK can be used as a guideline in presenting financial reports that have benefits to facilitate UMKM perpetrators in obtaining financing from banks and is useful as an evaluation of business performance. There are several items that affect level understanding of UMKM in compiling financial reports including accounting understanding level, quality of human resources, size of enterprise, information provision and socialization. This study looks at how level of comprehension of accounting, human resources quality, measurement of enterprises and informational notifications to SMEs in compilation of financial reports based on 100 UMKM EMKM in Bogor City. The findings indicate that the level of accounting comprehension and quality of natural resources influence on understanding UMKM to compile financial report based on EMKM SAK. Whereas the size of business and the dissemination of knowledge and socialization have no impact on understanding of the UMKM into compiling Financial Report.